2014
DOI: 10.1016/j.ajog.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A chemoresponse assay for prediction of platinum resistance in primary ovarian cancer

Abstract: Assay resistance to carboplatin is strongly associated with shortened PFS among advanced-stage epithelial ovarian cancer patients treated with carboplatin + paclitaxel therapy, supporting use of this assay to identify patients likely to experience early recurrence on standard platinum-based therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…This study demonstrates that assay resistance to carboplatin is associated with reduced PFS in EOC patients treated with standard of care carboplatin/paclitaxel, supporting the assay’s ability to identify platinum-resistant patients. Furthermore, of those patients who were resistant to carboplatin in vitro, 59 % of them displayed assay sensitivity (S or IS) to at least one other agent [48]. …”
Section: Chemofxmentioning
confidence: 99%
“…This study demonstrates that assay resistance to carboplatin is associated with reduced PFS in EOC patients treated with standard of care carboplatin/paclitaxel, supporting the assay’s ability to identify platinum-resistant patients. Furthermore, of those patients who were resistant to carboplatin in vitro, 59 % of them displayed assay sensitivity (S or IS) to at least one other agent [48]. …”
Section: Chemofxmentioning
confidence: 99%
“…The poor prognosis of epithelial ovarian cancer (EOC) is due to a combination of the aggressive characteristics of the disease and an unpredictable response to front-line therapy, further compounded by late detection of the disease and resistance of ovarian cancers to current treatments (3). The primary treatment for EOC consists of aggressive cytoreductive surgery, followed by chemotherapy with platinum and taxane (4). Although platinum and taxane combination remains the standard treatment for EOC, new drug combinations (5) as well as different administration schedules (6) are being tested and might be reasonable options for first-line treatment of women with advanced EOC.…”
Section: Introductionmentioning
confidence: 99%
“…Krivak and colleagues reported that in vitro assay resistance to carboplatin is associated with decreased PFS in women with advanced-stage EOC treated with platinum based therapy. Specifically, women whose tumor specimens demonstrated in vitro platinum resistance were at higher risk for disease progression compared to those with sensitive or intermediate sensitive assay results (median PFS: 11.8 vs 16.6 months, respectively, P  < .001) [6]. In addition, our group compared in vitro assay response between Type I and Type II EOC and found that, despite the dogmatic belief that Type I EOC are chemoresistant, the majority (86%) of Type I tumors were chemosensitive to at least one cytotoxic agent and 35.7% were pan-S to all 7 agents tested [14].…”
Section: Discussionmentioning
confidence: 99%
“…Details regarding the particular chemoresponse assay used in this study (ChemoFx®, Helomics Corporation, Pittsburgh, PA) have been described elsewhere [6, 7]. Assay preparation included an immunocytochemistry step to aid in the confirmation that cells were of epithelial, rather than stromal, origin.…”
Section: Methodsmentioning
confidence: 99%